Analysis of Surface Roughness Value When Drilling Magnesiumaz31 Using Taghuci Method - Gusri Akhyar Ibrahim; Arinal Hamni; Sri Maria Puji Lestari (Universitas Lampung, 2017)
Magnesium alloy is one of super alloys material which wide used in manufacturing of automotive, biomedic, sport and electronic components. It was due to very light and resistent to corrosion. Surface roughness value has an important role to estabilish the quality of components. To produce a good surface roughness of machined surface, one of the important thing depends on the friction between the cutting tool and workpiece material when cutting process occurred. The aim of this paper is to analyse the surface roughness values of machined surface when drilling of magnesium alloy AZ31 using design of experiment of Taguchi Method. The experimental trials took place at cutting rotation of 635, 970 and 1420 rpm, feed rate of 0.10, 0.18 and 0.24 mm/rev, diameter tool of 10, 12 and 14 mm. The cutting of magnesium alloy was done by using a convensional drilling machine with TCA –35Erlo. Analysis of variance on the data of surface roughness value was done to get which factor is the most significant. The result shows that the feed rate is the most significant factor that contributed on the surface rougness value of machined surface. The minimum surface roughness value was attained at cutting rotation of 970 rpm, feed rate of 0.10 mm/rev and diameter of tool of 14 mm. Therefore, it can be stated that selecting the low feed rate factor produced low surface roughness value. Another hand, using high cutting rotation resulted low surface roughness value.Keywords—drilling, surface roughness, magnesiun AZ31,Taguchi Method